Limbah Kayu dan Kertas Bekas Untuk Pulp Kertas - Sarbin; Iskandar; Abdul Rasyid Zarta; Noorhamsyah; Arini Rajab (Poltanesa, 2021)
His study aims to analyze the extent to which a mixture of wood waste and used newsprint can be used as raw material for making paper.This study used a completely randomized design with two replications. where the treatment given is a mixture composition between waste wood pulp and old newsprint pulp, each consisting of 0 : 100% (A), 30% 70% (B), 50% : 50% (C), 70% : 30% (D) and 100% : 0% (E) of oven-dry weight of pulp per sheet of paperThe physical properties of paper pulp tested in the form of tear index, tensile index, crack index and folding resistance significantly affect the composition of the mixture of wood waste and used newsprint.The value of tear index, tensile index and folding resistance tend to decrease with the increase in the percentage of used newsprint to the composition of the mixture, while the value of the crack index increases. Wood waste and used newsprint can be used as raw materials in pulp and paper manufacture, especially in the treatment of mixed composition C (50%:50%.)